SEJARAH PERKEMBANGAN PGRI RIAU TAHUN 1961-2015 - Suci Purnandes; Isjoni Isjoni; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The history of PGRI Riau is a struggle of the organization of teachers formed in 1961 to advance the welfare of teachers and to pioneer the education world in Riau. Until 2015 PGRI Riau continues to grow well and promote education in Riau this. The purpose of this research is 1) to know the background of the development of PGRI Riau in 1961-2015. 2) to know the progress of PGRI Riau from time to time. 3) to know the impact of PGRI Riau in 1961-2015. The method used in this research is the historical method of qualitative approach. Data obtained from interviews and then analyzed in their own language. The location of the research is in Riau teacher building (GGR/ Gedung Guru Riau) Pekanbaru. The time of study began after the decree issued by the dean of teacher faculty of education and education of Riau University. Data collection techniques used are observation and interview techniques, surveys, and documentation. The results of the study provide knowledge to us that PGRI Riau is the result of teacher struggle to advance education in Riau.Keywords: PGRI Riau, organization of struggle